Productive performance and economic evaluation of tambaqui roelo in excavated fishponds, Manaus, Brazil - Costa, Jesaias Ismael (2018)
Tambaqui is the most widely-cultivated native fish species in Brazil. Although most production occurs in fish ponds, the species is also raised resevoirs, stream channels and net tanks. Despite its high yield and productive potential, cultivation of this species is not always economically viable. Consequently, the current study aimed to provide a technical and economic evaluation of tambaqui (Colossoma macropomum) production in the metropolitan region of Manaus. Eight projects were selected and, through a semi-structured questionnaire, production phases, production cycles, management adopted, infrastructure used, productive indexes and fiscal investment were analysed. Together this allowed total operational cost (TCO) and profitability indicators to be calculated. Stocking density used influenced apparent feed conversion, specific growth rate and final mean weight. Feed was the key item in the TOC, comprising 69.63%, followed by labor and depreciation. Producers sell to: cold-store companies (R$ 4.10 kg-1), markets (R$ 7.30 kg-1), direct consumers (R$ 10.00 kg-1), supermarkets (R$ 6.20 kg-1) and intermediates (R$ 5.50 kg-1). In general, the production of tambaqui proved to be fiscally viable, with a profitability index higher than 20%, and success being strongly related to the marketing channel used, sale price and price of feed.